Electrode assembly, preparation method thereof, and battery

By setting a functional layer containing fibrous solid electrolyte and niobium-based oxide nanoparticles between the negative electrode sheet and the separator of the battery, the problem of insufficient fast charging performance of the negative electrode and the reaction between the positive electrode and the negative electrode is solved, and higher thermal stability and safety performance are achieved.

CN119181840BActive Publication Date: 2025-03-21JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411435354.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-03-21
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

In the prior art, the negative electrode fast charging performance is insufficient and the positive electrode or positive electrode current collector aluminum foil reacts with the negative electrode, affecting the battery safety performance.

Method used

A functional layer is arranged between the negative electrode sheet and the separator. The functional layer contains fibrous solid electrolyte and niobium-based oxide nanoparticles, and the niobium-based oxide nanoparticles are adsorbed on the surface of the fibrous solid electrolyte.

Benefits of technology

It improves the negative electrode fast charging performance of the battery, enhances the thermal stability of the battery cell, avoids the contact reaction between the positive electrode and the negative electrode, and improves the safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181840B_ABST
    Figure CN119181840B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of new energy batteries, and specifically to an electrode assembly and a preparation method thereof and a battery, wherein the electrode assembly comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein a functional layer is provided between the negative electrode sheet and the separator; wherein the functional layer contains a fibrous solid electrolyte and niobium-based oxide nanoparticles, and at least part of the niobium-based oxide nanoparticles are adsorbed on the surface of the fibrous solid electrolyte. The battery of the present invention can improve the thermal stability of a high energy density battery cell, accelerate the migration of lithium ions, and enhance the fast charging performance of the battery through the functional layer containing fibrous solid electrolyte and niobium-based oxide nanoparticles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy batteries, and in particular to an electrode assembly and a preparation method thereof, and a battery. Background Art

[0002] Since the commercial application of lithium-ion batteries, they have been widely used in portable electronic products, electric vehicles and energy storage devices due to their high voltage, high energy density and long cycle life. Solid electrolytes are used in solid-state batteries. Compared with traditional liquid electrolytes, solid electrolytes have the advantages of high safety, high energy density, good cycle performance and wide operating temperature range. The solid electrolyte and the electrode material are connected in a solid state, so the effective contact between the electrode and the electrolyte is weak, the ion transmission kinetics in the solid material is low, and the interface impedance is too large. Semi-solid batteries are hybrid solid-liquid lithium batteries in the lithium-ion battery segment. Both solid electrolytes and liquid electrolytes exist in their cells, which can better take into account the advantages of both and achieve intrinsic safety.

[0003] Compared with traditional fuel vehicles, the charging time of electric vehicles is still one of the bottlenecks for popular use. Although the electrolyte is the most significant factor affecting the intrinsic fast charging ability of the battery cell, under high current charging conditions, a large number of lithium ions will quickly and simultaneously escape from the positive electrode and embed into the negative electrode, causing polarization of the negative electrode. If the negative electrode potential drops below 0V, the lithium ions cannot be embedded in the negative electrode and precipitate on the negative electrode surface, resulting in an increase in irreversible capacity decay, which can seriously cause safety problems. Therefore, optimizing the negative electrode structure and material system is crucial to improving the diffusion capacity of lithium ions. Natural graphite has a high specific capacity, but a small interlayer spacing, and is prone to volume expansion during the lithium extraction process, which affects the cycle performance. Currently, most of the negative electrodes have good comprehensive performance artificial graphite.

[0004] In the semi-solid battery technology route, the most commonly used method is to coat the diaphragm surface with a single or double-sided, single or composite solid electrolyte. Patent document CN117334993A introduces a solid electrolyte coating and a positive electrode material coating or a solid electrolyte into the diaphragm surface to improve the battery cell cycle performance and safety performance, but the improvement effect on thermal runaway is limited. In order to improve fast charging, patent document CN108461753A proposes to use carbon nanotubes and activated carbon as conductive agents at the same time to improve power density, and add negative electrode film-forming additives to the slurry to help form a stable SEI film, but a high proportion of conductive agents is difficult to disperse and easy to agglomerate. Summary of the invention

[0005] In view of this, the present invention is committed to providing an electrode assembly, a preparation method thereof and a battery to improve the fast charging performance of the negative electrode in the prior art, and to solve the problem in the prior art that the positive electrode or the positive electrode current collector aluminum foil reacts with the negative electrode, affecting the safety performance of the battery.

[0006] In order to solve the above technical problems, this application is implemented as follows:

[0007] A first aspect of the present invention provides an electrode assembly, the electrode assembly comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein a functional layer is provided between the negative electrode sheet and the separator;

[0008] The functional layer contains a fibrous solid electrolyte and niobium-based oxide nanoparticles, and at least a portion of the niobium-based oxide nanoparticles are adsorbed on the surface of the fibrous solid electrolyte.

[0009] Optionally, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector, and the functional layer is disposed on the surface of the negative electrode active material layer away from the negative electrode current collector.

[0010] Optionally, the thickness of the functional layer is 2-15 μm; and / or, based on the total mass of the functional layer, the content of the fibrous solid electrolyte is 40-60 wt %, and the content of the niobium-based oxide nanoparticles is 40-60 wt %.

[0011] Optionally, the diameter of the fiber-like solid electrolyte is 50 nm to 2 μm; and / or, the length of the fiber-like solid electrolyte is 5 to 20 μm; and / or, the specific surface area of ​​the fiber-like solid electrolyte is 45 to 70 m 2 / g; and / or, the porosity of the fibrous solid electrolyte is 3-7%; and / or, the pore size of the fibrous solid electrolyte is 10-20nm.

[0012] Optionally, the fibrous solid electrolyte comprises fast ion conductor nanofibers; and the fast ion conductor nanofibers comprise Li3N.

[0013] Optionally, the particle size of the niobium-based oxide nanoparticles is 10-100 nm; and / or the specific surface area of ​​the niobium-based oxide nanoparticles is 8-20 m 2 / g; and / or, the niobium-based oxide nanoparticles are selected from Nb2O5, TiNb x O 2+2.5x and at least one of M-Nb-O; wherein, 0<x≤12; the metal element M is selected from at least one of La, Cr, Ga, Fe, Zr, and Mg.

[0014] Optionally, the niobium-based oxide nanoparticles are La-Nb-O; the La-Nb-O is selected from La3NbO7, LaNb5O 14 、LaNbO4、La2Nb 12 O 33and at least one of LaNb3O9.

[0015] A second aspect of the present invention provides a method for preparing an electrode assembly, the method comprising the following steps:

[0016] S1. Mixing niobium-based oxide and fibrous solid electrolyte and subjecting them to ball milling to obtain a mixed powder; heating the mixed powder in a protective atmosphere to obtain a composite material; mixing the composite material with a solvent and subjecting them to dispersion to obtain a functional slurry;

[0017] S2, applying the functional slurry on the surface of the negative electrode plate to form a functional layer; and / or, applying the functional slurry on the surface of the separator to form a functional layer;

[0018] S3. Prepare the positive electrode sheet, the separator and the negative electrode sheet into an electrode assembly, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, and the functional layer is provided between the separator and the negative electrode sheet.

[0019] Optionally, in step S1, the conditions of the heating treatment include: a temperature of 600~800°C and a time of 120~168h; and / or, the dispersion treatment is ultrasonic dispersion, and the conditions of the ultrasonic dispersion include: an ultrasonic frequency of 15~25KHz, a dispersion time of 2~4h, and a power of 1-4KW; and / or, the solvent is polyvinylidene fluoride glue.

[0020] A third aspect of the present invention provides a battery, the battery comprising an electrode assembly, the electrode assembly being the electrode assembly described above and / or an electrode assembly prepared according to the method described above.

[0021] Through the above technical solution, the beneficial technical effects of the present invention are:

[0022] (1) The battery assembly of the present invention is provided with a functional layer between the negative electrode plate and the separator. Niobium-based oxide has extremely high thermal stability, which can avoid the internal short circuit caused by the contact between the aluminum foil and the negative electrode, thereby improving the safety performance of the battery cell.

[0023] (2) The high porosity and high specific surface area of ​​the fibrous solid electrolyte and niobium-based oxide nanoparticles in the present invention can quickly absorb and retain the electrolyte, thereby improving the electrolyte wetting effect of the high compaction density negative electrode and improving the interface.

[0024] (3) The fast ion conductor nanofibers Li3N and niobium-based oxide nanoparticles in the present invention can form a composite interface insulating layer to protect the SEI film, increase the decomposition temperature of the SEI film when thermal runaway occurs, and enhance the protective effect on the negative electrode interface. In addition, the composite interface insulating layer can induce the deposition of lithium ions, preventing the lithium ions that are deintercalated under high current charging from precipitating on the negative electrode surface to form lithium dendrites.

[0025] (4) When the lithium-ion battery operates at a voltage below 0.98V, the main components of the SEI film include Li2CO3, LiF and Li2O, and the main diffusion carrier in Li2CO3 is the excess lithium ion interstitial; above 3.98V, lithium ion vacancies become the main type of diffusion carrier. The fast ion conductor nanofibers Li3N and niobium-based oxide nanoparticles contained in the functional layer of the present invention can increase the concentration of diffusion carriers at different voltages and improve the transportation performance of lithium ions through Li2CO3.

[0026] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention.

[0028] Figure 1 Shown is a first electron microscope image of the negative electrode sheet with a functional layer of Example 1.

[0029] Figure 2 Shown is a second electron microscope image of the negative electrode sheet with a functional layer of Example 1.

[0030] Figure 3 Shown is a third electron microscope image of the negative electrode sheet with a functional layer of Example 1.

[0031] Figure 4 Shown is a schematic diagram of a negative electrode sheet with a functional layer in Example 1. DETAILED DESCRIPTION

[0032] The present invention discloses an electrode assembly, a method for preparing the same, and a battery. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit, and scope of the present invention to implement and apply the technology of the present invention.

[0033] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0034] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0035] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0036] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0037] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0038] In order to solve the problem in the prior art that the positive electrode or the positive electrode current collector aluminum foil reacts with the negative electrode and affects the safety performance of the battery, the present invention adopts the following technical solution:

[0039] A first aspect of the present invention provides an electrode assembly, the electrode assembly comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein a functional layer is provided between the negative electrode sheet and the separator;

[0040] The functional layer contains a fibrous solid electrolyte and niobium-based oxide nanoparticles, and at least a portion of the niobium-based oxide nanoparticles are adsorbed on the surface of the fibrous solid electrolyte.

[0041] The electrode assembly of the present invention is provided with a functional layer between the negative electrode plate and the diaphragm, and the functional coating contains fibrous solid electrolyte and niobium-based oxide nanoparticles. Among them, the fibrous solid electrolyte can provide a long-range migration path and accelerate the migration speed of ions; niobium-based oxide has a higher heat resistance temperature, and nano-sized niobium-based oxide has a lower energy barrier for ions to escape from nano-sized particles while having a higher heat resistance temperature, and a faster migration speed. Through the combined action of fibrous solid electrolyte and niobium-based oxide nanoparticles, on the one hand, the thermal stability of high-energy density batteries can be improved, the decomposition temperature of SEI film during thermal runaway can be increased, combustible gases can be effectively absorbed, the reaction between the positive and negative electrodes can be blocked, and thermal runaway can be avoided; on the other hand, the migration of lithium ions can be accelerated, and the solid electrolyte phase interface layer (SEI) on the surface of the negative electrode can be quickly passed into the graphite or silicon-carbon layer, thereby improving the fast charging performance and avoiding lithium precipitation caused by high current charging.

[0042] The functional layer of the present invention is disposed between the negative electrode plate and the separator. Exemplarily, the functional layer can be disposed on the surface of the negative electrode plate, that is, on the surface of the negative electrode active material layer away from the negative electrode current collector. Exemplarily, the functional layer can be disposed on the surface of the separator close to the negative electrode plate.

[0043] In a preferred embodiment of the present invention, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector, and the functional layer is disposed on the surface of the negative electrode active material layer away from the negative electrode current collector. In this embodiment, the functional layer is disposed on the surface of the negative electrode active material layer away from the negative electrode current collector, which is more conducive to the functional layer covering the negative electrode active material layer, so as to further avoid contact between the negative electrode active material layer and the positive electrode, thereby improving the safety performance of the battery assembly.

[0044] In a preferred embodiment of the present invention, the negative electrode active material in the negative electrode active material layer includes graphite and an optional silicon-carbon compound and / or a silicon-oxygen compound. Exemplarily, the silicon-carbon compound may be silicon carbide; the silicon-oxygen compound may be at least one of SiO, SiO2 and Si2O6.

[0045] In the present invention, if the content of silicon-carbon compounds and / or silicon-oxygen compounds in the negative electrode active material is too high, the energy density of the battery cell may be too high, and thermal runaway may occur easily; if the content of silicon-carbon compounds and / or silicon-oxygen compounds in the negative electrode active material is too low, the energy density of the battery cell may be too low, and the ideal technical effect cannot be achieved. Further preferably, based on the total mass of the negative electrode active material, the content of silicon-carbon compounds and / or silicon-oxygen compounds in the negative electrode active material is 5 to 20 wt%, preferably 5 to 15 wt%.

[0046] According to the present invention, the thickness of the functional layer may be 2 to 15 μm. Exemplarily, the thickness of the functional layer may be any value among 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm and 15 μm, or any value within the range of values ​​formed by any two of the above values. In the present invention, if the thickness of the functional layer is too large, the energy density of the battery cell will be reduced due to the high density of the material itself; if the thickness of the functional layer is too small, the ideal safety performance may not be obtained. Preferably, the thickness of the functional layer is 5 to 12 μm.

[0047] In a specific embodiment of the present invention, the thickness of the functional layer can be adjusted according to the content of the silicon-carbon compound and / or silicon-oxygen compound in the negative electrode active material. For example, when the content of the silicon-carbon compound and / or silicon-oxygen compound is less than 10wt%, the thickness of the functional layer is preferably greater than 5μm; when the content of the silicon-carbon compound and / or silicon-oxygen compound is 10-15wt%, the thickness of the functional layer is preferably greater than 10μm; when the content of the silicon-carbon compound and / or silicon-oxygen compound is 15-20wt%, the thickness of the functional layer is preferably greater than 15μm.

[0048] In the present invention, the minimum width of the functional layer is slightly larger than the width of the positive electrode, and the minimum length of the functional layer is slightly larger than the length of the positive electrode. In one embodiment, in order to ensure the safety of the battery assembly, the length of the functional layer is longer than the positive electrode in the length direction of the negative electrode sheet, and the width of the functional layer is longer than the positive electrode in the width direction of the negative electrode sheet. In another preferred embodiment, in order to improve the safety performance of the battery assembly, the functional layer fully covers the negative electrode active material layer to avoid contact points between the negative electrode active material layer and the positive electrode during short circuit.

[0049] According to the present invention, based on the total mass of the functional layer, the content of the fibrous solid electrolyte can be 40-60wt%, and the content of the niobium-based oxide nanoparticles can be 40-60wt%. The functional layer at this ratio has better fast charging performance while ensuring that the battery core has good thermal stability.

[0050] According to the present invention, the diameter of the fibrous solid electrolyte can be 50nm~2μm. In the present invention, the term "diameter of the fibrous solid electrolyte" specifically refers to the outer diameter of the fibrous solid electrolyte along the cross-sectional direction. Exemplarily, the diameter of the fibrous solid electrolyte can be any value among 50nm, 100nm, 400nm, 600nm, 800nm, 1μm and 2μm, or any value within the range of values ​​composed of any two of the above values. In the present invention, if the diameter of the fibrous solid electrolyte is too large, the stability of the solid electrolyte itself will be reduced, the material structure will collapse easily, and the ionic conductivity will decrease; if the diameter of the fibrous solid electrolyte is too small, a one-dimensional state will be formed, which is not conducive to the migration of ions. Preferably, the diameter of the fibrous solid electrolyte is 200 nm ~1.5μm.

[0051] According to the present invention, the length of the fibrous solid electrolyte can be 5 to 20 μm. Exemplarily, the length of the fibrous solid electrolyte can be any value among 5 μm, 7.5 μm, 10 μm, 12.5 μm, 15 μm, 17.5 μm and 20 μm, or any value within the range of any two of the above values. In the present invention, if the length of the fibrous solid electrolyte is too large, it is easy to cause the solid electrolyte itself to break; if the length of the fibrous solid electrolyte is too small, the long-range migration effect of the fibrous solid electrolyte will be reduced. Preferably, the length of the fibrous solid electrolyte is 8 to 15 μm.

[0052] According to the present invention, the specific surface area of ​​the fibrous solid electrolyte can be 45-70 m 2 / g. Exemplarily, the specific surface area of ​​the fibrous solid electrolyte can be 45 m 2 / g, 50 m 2 / g, 55 m 2 / g, 60 m 2 / g, 65 m 2 / g and 70m 2 / g or any value in the range of any two of the above values. In the present invention, if the specific surface area of ​​the fibrous solid electrolyte is too large, in a specific embodiment, it may be necessary to add more binder, which may increase the internal resistance of the electrical component; if the specific surface area of ​​the fibrous solid electrolyte is too small, the channels for ion migration are relatively small, thereby affecting the ion mobility. Preferably, the specific surface area of ​​the fibrous solid electrolyte is 50~65m 2 / g.

[0053] According to the present invention, the porosity of the fibrous solid electrolyte can be 3-7%. The appropriate porosity of the fibrous solid electrolyte can provide a suitable migration channel and optimize the flow required for lithium battery excitation. Exemplarily, the porosity of the fibrous solid electrolyte can be any value among 3%, 4%, 5%, 6% and 7%, or any value within the range of any two of the above values.

[0054] According to the present invention, the pore size of the fibrous solid electrolyte can be 10-20 nm. The appropriate pore size of the fibrous solid electrolyte can provide a suitable migration channel and optimize the flow required for lithium battery excitation. Exemplarily, the pore size of the fibrous solid electrolyte can be any value among 10 nm, 12.5 nm, 15 nm, 17.5 nm and 20 nm or any value within the range of any two of the above values.

[0055] In the present invention, the fibrous solid electrolyte includes fast ion conductor nanofibers, which have an ionic conductivity close to that of liquid electrolytes and can further accelerate the migration speed of ions. As a preferred embodiment of the present invention, the fast ion conductor nanofibers include Li3N. Nanofibrous Li3N is highly stable and has excellent performance, and can provide a stable elongated tubular skeleton structure; niobium-based oxide nanoparticles are adsorbed on the surface of Li3N, and through the organic combination of point-like niobium-based oxide nanoparticles and chain-like nanofibrous Li3N, the short-range or long-range rapid migration of lithium ions can be satisfied.

[0056] In the present invention, the niobium-based oxide nanoparticles (001) have a crystal plane d=0.39nm, which is larger than the lithium ion diameter of 0.152nm. The relatively large specific surface area and pore size allow the active material of the electrode to have more sufficient contact with the electrolyte, providing an effective diffusion channel for lithium ions and reducing the stress of lithium ions during the embedding and extraction process. Nanocomposites with rich pore structures and large specific surface areas have a high improvement in the dynamics of lithium ions and the rate performance of materials.

[0057] According to the present invention, the particle size of the niobium-based oxide nanoparticles may be 10 to 100 nm. Exemplarily, the particle size of the niobium-based oxide nanoparticles may be any value among 10 nm, 12.5 nm, 15 nm, 17.5 nm and 20 nm or any value within the range of values ​​composed of any two of the above values. In the present invention, if the particle size of the niobium-based oxide nanoparticles is too large, the specific surface area of ​​the niobium-based oxide will be reduced, thereby affecting the migration distance and energy barrier of the ions; if the particle size of the niobium-based oxide nanoparticles is too small, the specific surface area of ​​the niobium-based oxide will be increased, and the van der Waals force that needs to be overcome for ion migration will be reduced, shortening the diffusion channel. Preferably, the particle size of the niobium-based oxide nanoparticles is 30 to 70 nm.

[0058] According to the present invention, the specific surface area of ​​the niobium-based oxide nanoparticles can be 8 to 20 m 2 / g. Exemplarily, the specific surface area of ​​the niobium-based oxide nanoparticles may be 8 m 2 / g, 10 m 2 / g, 12 m 2 / g, 14 m 2 / g, 16 m 2 / g, 18m 2 / g and 20 m 2 / g or any value in the range of values ​​formed by any two of the above values. In the present invention, if the specific surface area of ​​the niobium-based oxide nanoparticles is too large, the van der Waals force that needs to be overcome by ion migration will be reduced, shortening the diffusion channel; if the specific surface area of ​​the niobium-based oxide nanoparticles is too small, the migration distance and energy barrier of the ions will be affected. Preferably, the specific surface area of ​​the niobium-based oxide nanoparticles is 8-12 m 2 / g.

[0059] According to the present invention, the niobium-based oxide nanoparticles have a special two-dimensional and Wadsley-Roth crystal shear structure, which can provide a three-dimensional open tunnel structure, which is conducive to lithium ion embedding and storage. The niobium-based oxide nanoparticles can be selected from Nb2O5, TiNb x O 2+2.5x and at least one of M-Nb-O; wherein, 0<x≤12; the metal element M can be selected from at least one of La, Cr, Ga, Fe, Zr, and Mg.

[0060] In a preferred embodiment of the present invention, the niobium-based oxide nanoparticles are La-Nb-O; Nb 5+ and La 3+The ionic electronegativity values ​​of La are 1.862 and 1.327 respectively. La doping can reduce orbital overlap and facilitate the diffusion of lithium ions. For example, the La-Nb-O can be selected from La3NbO7, LaNb5O 14 、LaNbO4、La2Nb 12 O 33 and at least one of LaNb3O9.

[0061] A second aspect of the present invention provides a method for preparing an electrode assembly, the method comprising the following steps:

[0062] S1. Mixing niobium-based oxide and fibrous solid electrolyte and subjecting them to ball milling to obtain a mixed powder; heating the mixed powder in a protective atmosphere to obtain a composite material; mixing the composite material with a solvent and subjecting them to dispersion to obtain a functional slurry;

[0063] S2, applying the functional slurry on the surface of the negative electrode plate to form a functional layer; and / or, applying the functional slurry on the surface of the separator to form a functional layer;

[0064] S3. Prepare the positive electrode sheet, the separator and the negative electrode sheet into an electrode assembly, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, and the functional layer is provided between the separator and the negative electrode sheet.

[0065] According to the present invention, in step S1, the conditions of the heating treatment may include: a temperature of 600~800°C and a time of 120~168h; and / or, the dispersion treatment may be ultrasonic dispersion, and the conditions of the ultrasonic dispersion may include: an ultrasonic frequency of 15~25KHz, a dispersion time of 2~4h, and a power of 1-4KW; and / or, the solvent may be polyvinylidene fluoride glue.

[0066] A third aspect of the present invention provides a battery, the battery comprising an electrode assembly, the electrode assembly being the electrode assembly described above and / or an electrode assembly prepared according to the method described above.

[0067] In a specific embodiment, the battery comprises an electrode assembly and an electrolyte, wherein the electrode assembly comprises a positive electrode sheet, a negative electrode sheet, a separator, and a functional layer disposed between the negative electrode sheet and the separator.

[0068] The positive electrode sheet applicable to the present invention may include at least one of ternary lithium positive electrode active materials, lithium iron phosphate positive electrode active materials, lithium cobalt oxide positive electrode active materials, lithium-rich manganese-based positive electrode active materials and lithium manganate positive electrode active materials. The diaphragm applicable to the present invention may include at least one of polypropylene (PP), polyethylene (PE) and polyimide (PI). The surface of the diaphragm of the present invention may have a single-sided or double-sided coating, and the coating material may include at least one of aluminum oxide, boehmite and solid electrolyte. The lithium salt of the electrolyte applicable to the present invention is lithium hexafluorophosphate LiPF6, and the solvent includes at least one of cyclic carbonate (EC) and chain carbonate (DMC / EMC / DEC).

[0069] The present invention is further described in detail by way of examples. The raw materials used in the examples can be obtained through commercial sources.

[0070] The diameter of Li3N used in the examples and comparative examples is 200 nm to 1.5 μm, the length is 8 to 15 μm, and the specific surface area is 50 to 65 m 2 / g, the porosity is 3~7%, and the pore size is 10~20nm.

[0071] The preparation method of the positive electrode sheet used in the embodiments and comparative examples includes: selecting NCM811 as the positive electrode active material, preparing a slurry of NCM811, conductive agent SP and polyvinylidene fluoride (PVDF) in a mass ratio of 98:1:1, coating the slurry on the surface of the current collector and drying it to obtain the positive electrode sheet.

[0072] The separator used in the examples and comparative examples was a polypropylene (PP) separator having a thickness of 10 μm.

[0073] Example 1

[0074] (1) Preparation of functional slurry: Niobium-based oxide LaNb5O 14 and Li3N in a mass ratio of 1:1 and then subjected to high-energy ball milling to obtain a mixed powder; the mixed powder is heated in a protective atmosphere to obtain a composite material LaNb5O 14 @Li3N. Among them, niobium-based oxide LaNb5O 14 The particle size is 80nm and the specific surface area is 20m 2 / g; the heating treatment is carried out in a heating furnace, and the heating conditions include: heating to 700°C, keeping warm for 5 to 7 days, and then cooling to room temperature. 14 @Li3N mixed with PVDF glue, LaNb5O 14The mixing mass ratio of @Li3N and PVDF glue is 1:0.1, and a planetary disperser with ultrasonic dispersion function is used for dispersion to obtain a functional slurry, wherein the ultrasonic frequency is 20KHz, the dispersion time is 3h, and the power is 3KW.

[0075] (2) Preparation of negative electrode sheet: Graphite, silicon oxide, conductive agent and binder are mixed to prepare negative electrode slurry, wherein the conductive agent is carbon black, the binder is a mixture of polyacrylic acid (PAA) and styrene-butadiene rubber (SBR), and the mixing ratio of PAA and SBR is 1:0.5. Based on the total mass of the negative electrode slurry, the content of graphite is 86.6wt%, the content of silicon oxide is 10wt%, the content of conductive agent is 1.2wt%, and the content of binder is 2.2wt%. The specific steps for preparing the negative electrode slurry are as follows: sodium carboxymethyl cellulose (CMC) powder is added to deionized water and dispersed for 4h to obtain CMC glue with a solid content of 1.6%, carbon black conductive agent is added and dispersed for 2h to obtain conductive glue, graphite and silicon oxide are added in turn, and high-speed dispersion is continued for 2h, and finally PAA and SBR binders are added, the viscosity is adjusted to the viscosity required for coating, and the slurry is coated on the surface of the copper current collector to obtain a negative electrode sheet. Figure 4 The schematic diagram of the negative electrode sheet prepared in this embodiment is shown; the electron microscope image of the negative electrode sheet under a 200x microscope is shown in FIG. Figure 1 , see the electron microscope image at 1770 times Figure 2 , see the electron microscope image at 2230 times Figure 3 .pass Figure 1 and Figure 4 It can be seen that the distribution of the functional layer and the active layer in the negative electrode sheet prepared in this embodiment is Figure 2 The thickness of the functional layer in the negative electrode can be measured by Figure 3 The morphological characteristics of the functional layer can be seen.

[0076] (3) Preparation of electrode assembly: The functional slurry is coated on the surface of the above-mentioned negative electrode sheet to form a functional layer, wherein the coating thickness is 5 μm. The positive electrode sheet, the separator and the negative electrode sheet are prepared into an electrode assembly, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, and there is a functional layer between the separator and the negative electrode sheet.

[0077] Example 2

[0078] The preparation of the functional slurry and the negative electrode sheet in this embodiment is the same as that in Embodiment 1. The difference is that in the preparation of the electrode assembly, the coating thickness of the functional layer is 2 μm.

[0079] Example 3

[0080] (1) Preparation of functional slurry: same as in Example 1.

[0081] (2) Preparation of negative electrode sheet: Graphite, silicon oxide, conductive agent and binder are mixed to prepare negative electrode slurry, wherein the conductive agent is carbon black, the binder is a mixture of polyacrylic acid (PAA) and styrene-butadiene rubber (SBR), and the mixing ratio of PAA and SBR is 1:0.5. Based on the total mass of the negative electrode slurry, the content of graphite is 76.6wt%, the content of silicon oxide is 20wt%, the content of conductive agent is 1.2wt%, and the content of binder is 2.2wt%. The specific steps for preparing the negative electrode slurry are as follows: sodium carboxymethyl cellulose (CMC) powder is added to deionized water and dispersed for 4h to obtain CMC glue with a solid content of 1.6%, carbon black conductive agent is added and dispersed for 2h to obtain conductive glue, graphite and silicon oxide are added in turn, and high-speed dispersion is continued for 2h, and finally PAA and SBR binders are added, the viscosity is adjusted to the viscosity required for coating, and the slurry is coated on the surface of the copper current collector to obtain a negative electrode sheet.

[0082] (3) Preparation of electrode assembly: The functional slurry is coated on the surface of the above-mentioned negative electrode sheet to form a functional layer, wherein the coating thickness is 10 μm. The positive electrode sheet, the separator and the negative electrode sheet are prepared into an electrode assembly, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, and there is a functional layer between the separator and the negative electrode sheet.

[0083] Example 4

[0084] The preparation of the functional slurry and the negative electrode sheet in this embodiment is the same as that in Embodiment 4. The difference is that in the preparation of the electrode assembly, the coating thickness of the functional layer is 15 μm.

[0085] Example 5

[0086] (1) Preparation of functional slurry: Nb2O5 and Li3N were mixed in a mass ratio of 1:1 and then subjected to high-energy ball milling to obtain a mixed powder; the mixed powder was heated in a protective atmosphere to obtain a composite material Nb2O5@Li3N. The particle size of Nb2O5 is 50nm and the specific surface area is 60m 2 / g; the heating treatment is carried out in a heating furnace, and the heating conditions include: heating to 700℃, keeping warm for 5-7 days, and then cooling to room temperature. The composite material Nb2O5@Li3N is mixed with PVDF glue, and the mixing mass ratio of Nb2O5@Li3N and PVDF glue is 1:0.1. A planetary disperser with ultrasonic dispersion function is used for dispersion to obtain a functional slurry, wherein the ultrasonic frequency is 20KHz, the dispersion time is 3h, and the power is 3KW.

[0087] (2) Preparation of negative electrode sheet: same as in Example 1.

[0088] (3) Preparation of electrode assembly: The functional slurry is coated on the surface of the above-mentioned negative electrode sheet to form a functional layer, wherein the coating thickness is 5 μm. The positive electrode sheet, the separator and the negative electrode sheet are prepared into an electrode assembly, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, and there is a functional layer between the separator and the negative electrode sheet.

[0089] Example 6

[0090] (1) Preparation of functional slurry: LaNb5O 14 and Li3N in a mass ratio of 1:1 and then subjected to high-energy ball milling to obtain a mixed powder; the mixed powder is heated in a protective atmosphere to obtain a composite material LaNb5O 14 @Li3N. Among them, LaNb5O 14 The particle size is 80nm and the specific surface area is 20m 2 / g; the heating treatment is carried out in a heating furnace, and the heating conditions include: heating to 700°C, keeping warm for 5 to 7 days, and then cooling to room temperature. 14 @Li3N mixed with PVDF glue, LaNb5O 14 The mixing mass ratio of @Li3N and PVDF glue is 1:0.1, and a planetary disperser with ultrasonic dispersion function is used for dispersion to obtain a functional slurry, wherein the ultrasonic frequency is 20KHz, the dispersion time is 3h, and the power is 3KW.

[0091] (2) Preparation of negative electrode sheet: Graphite, silicon oxide, conductive agent and binder are mixed to prepare negative electrode slurry, wherein the conductive agent is carbon black, the binder is a mixture of polyacrylic acid (PAA) and styrene-butadiene rubber (SBR), and the mixing ratio of PAA and SBR is 1:0.5. Based on the total mass of the negative electrode slurry, the content of graphite is 86.6wt%, the content of silicon oxide is 10wt%, the content of conductive agent is 1.2wt%, and the content of binder is 2.2wt%. The specific steps for preparing the negative electrode slurry are as follows: sodium carboxymethyl cellulose (CMC) powder is added to deionized water and dispersed for 4h to obtain CMC glue with a solid content of 1.6%, carbon black conductive agent is added and dispersed for 2h to obtain conductive glue, graphite and silicon oxide are added in turn, and high-speed dispersion is continued for 2h, and finally PAA and SBR binders are added, the viscosity is adjusted to the viscosity required for coating, and the slurry is coated on the surface of the copper current collector to obtain a negative electrode sheet.

[0092] (3) Preparation of electrode assembly: The functional slurry is coated on the surface of the separator with a coating thickness of 2 μm, with the coating surface facing the negative electrode side. The positive electrode sheet, the separator and the negative electrode sheet are prepared into an electrode assembly, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, and there is a functional layer between the separator and the negative electrode sheet.

[0093] Comparative Example 1

[0094] Graphite, silicon oxide, a conductive agent and a binder are mixed to prepare a negative electrode slurry, wherein the conductive agent is carbon black, the binder is a mixture of polyacrylic acid (PAA) and styrene-butadiene rubber (SBR), and the mixing ratio of PAA and SBR is 1:0.5. Based on the total mass of the negative electrode slurry, the content of graphite is 86.6wt%, the content of silicon oxide is 10wt%, the content of the conductive agent is 1.2wt%, and the content of the binder is 2.2wt%. The specific steps for preparing the negative electrode slurry are as follows: sodium carboxymethyl cellulose (CMC) powder is added to deionized water and dispersed for 4h to obtain a CMC glue with a solid content of 1.6%, a carbon black conductive agent is added and dispersed for 2h to obtain a conductive glue, graphite and silicon oxide are added in turn, and high-speed dispersion is continued for 2h, and finally PAA and SBR binders are added, the viscosity is adjusted to the viscosity required for coating, and the slurry is coated on the surface of the copper current collector to obtain a negative electrode sheet.

[0095] The positive electrode sheet, the separator and the negative electrode sheet are prepared into an electrode assembly.

[0096] Comparative Example 2

[0097] (1) Preparation of functional slurry: LaNb5O 14 、Li7La3Zr2O 12 Mixed with PVDF glue, LaNb5O 14 、Li7La3Zr2O 12 The mass ratio of the mixture with PVDF glue is 1:1:0.1, and a planetary disperser with ultrasonic dispersion function is used for dispersion to obtain a functional slurry, wherein the ultrasonic frequency is 20KHz, the dispersion time is 3h, and the power is 3KW.

[0098] (2) Preparation of negative electrode sheet: same as in Example 1.

[0099] (3) Preparation of electrode assembly: The functional slurry is coated on the surface of the above-mentioned negative electrode sheet to form a functional layer, wherein the coating thickness is 5 μm. The positive electrode sheet, the separator and the negative electrode sheet are prepared into an electrode assembly, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, and there is a functional layer between the separator and the negative electrode sheet.

[0100] Comparative Example 3

[0101] (1) Preparation of functional slurry: Li3N and PVDF glue were mixed in a mass ratio of 1:0.1, and dispersed using a planetary disperser with ultrasonic dispersion function to obtain a functional slurry, wherein the ultrasonic frequency was 20 kHz, the dispersion time was 3 h, and the power was 3 kW.

[0102] (2) Preparation of negative electrode sheet: same as in Example 1.

[0103] (3) Preparation of electrode assembly: The functional slurry is coated on the surface of the above-mentioned negative electrode sheet to form a functional layer, wherein the coating thickness is 5 μm. The positive electrode sheet, the separator and the negative electrode sheet are prepared into an electrode assembly, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, and there is a functional layer between the separator and the negative electrode sheet.

[0104] Comparative Example 4

[0105] (1) Preparation of functional slurry: Nb2O5 and PVDF glue were mixed in a mass ratio of 1:0.1, and dispersed using a planetary disperser with ultrasonic dispersion function to obtain a functional slurry, wherein the ultrasonic frequency was 20 kHz, the dispersion time was 3 h, and the power was 3 kW.

[0106] (2) Preparation of negative electrode sheet: same as in Example 1.

[0107] (3) Preparation of electrode assembly: The functional slurry is coated on the surface of the above-mentioned negative electrode sheet to form a functional layer, wherein the coating thickness is 5 μm. The positive electrode sheet, the separator and the negative electrode sheet are prepared into an electrode assembly, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, and there is a functional layer between the separator and the negative electrode sheet.

[0108] Test Example 1

[0109] The electrode assemblies obtained in Examples 1 to 6 and Comparative Examples 1 to 4 were used to prepare battery cells, and performance tests were performed on the prepared battery cells. The test results are shown in Table 1.

[0110] Among them, the preparation method of the battery cell includes: the preparation method of the battery cell includes two processes of winding and lamination, which can be made into three battery forms: cylindrical, soft-pack and square, including positive electrode, negative electrode, diaphragm, electrolyte and other mechanical components.

[0111] The test method for 1C charging constant current ratio is: 25℃, 1C constant current constant voltage charging, charging to 4.2V, constant voltage section cut-off current is 0.05C.

[0112] The test method for the 3C charging constant current ratio is: 25℃, 3C constant current and constant voltage charging, charging to 4.2V, and the cut-off current in the constant voltage section is 0.05C.

[0113] The test method of the puncture test is as follows: the diameter of the steel needle is 3mm, the needle tip is conical, the angle is 30°, the puncture speed is 3mm / s, and the steel needle penetrates vertically into the large surface of the battery cell.

[0114] Table 1

[0115]

[0116] It can be seen from the data in Table 1 that the electrode assembly of Comparative Example 1 is not provided with a functional layer and cannot pass the puncture safety test; the electrode assembly of Comparative Example 3 is only provided with a Li3N functional layer and cannot pass the puncture safety test. Under the same silicon-oxygen ratio and functional layer thickness, the functional layer of Example 2 is arranged on the surface of the negative electrode plate, and the functional layer of Example 6 is arranged on the surface of the diaphragm. Compared with Example 6, Example 2 has better performance and can pass the puncture test; in Examples 4 and 5, when the silicon-carbon ratio reaches 20%, the negative electrode gram capacity is high, and the energy density of the battery cell monomer is greatly improved. The 10μm functional coating in Example 4 cannot improve the puncture safety, and the coating thickness of 15μm in Example 5 can improve the safety of the battery cell. When the thickness of the functional layer is greater than 5μm, the functional layer does not significantly improve the performance of the negative electrode fast charge, and excessive thickness (greater than 10μm) may even weaken the fast charge performance.

[0117] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An electrode assembly, characterized in that: The electrode assembly comprises a positive electrode sheet, a negative electrode sheet and a separator, and a functional layer is provided between the negative electrode sheet and the separator; Wherein, the functional layer contains a fibrous solid electrolyte and niobium-based oxide nanoparticles, and at least a portion of the niobium-based oxide nanoparticles are adsorbed on the surface of the fibrous solid electrolyte; The fibrous solid electrolyte comprises fast ion conductor nanofibers; the fast ion conductor nanofibers comprise Li3N; The niobium-based oxide nanoparticles are La-Nb-O; the La-Nb-O is selected from La3NbO7, LaNb5O 14 、LaNbO4、La2Nb 12 O 33 and at least one of LaNb3O9.

2. The electrode assembly according to claim 1, characterized in that: The negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer arranged on the surface of the negative electrode current collector, and the functional layer is arranged on the surface of the negative electrode active material layer away from the negative electrode current collector.

3. The electrode assembly according to claim 1, characterized in that: The thickness of the functional layer is 2-15 μm; And / or, based on the total mass of the functional layer, the content of the fibrous solid electrolyte is 40-60wt%, and the content of the niobium-based oxide nanoparticles is 40-60wt%.

4. The electrode assembly according to claim 1, characterized in that: The diameter of the fibrous solid electrolyte is 50nm~2μm; And / or, the length of the fibrous solid electrolyte is 5 to 20 μm; And / or, the specific surface area of ​​the fibrous solid electrolyte is 45-70 m 2 / g; And / or, the porosity of the fibrous solid electrolyte is 3-7%; And / or, the pore size of the fibrous solid electrolyte is 10-20 nm.

5. The electrode assembly according to claim 1, characterized in that: The particle size of the niobium-based oxide nanoparticles is 10-100 nm; And / or, the specific surface area of ​​the niobium-based oxide nanoparticles is 8 to 20 m 2 / g.

6. A method for preparing the electrode assembly according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: S1. Mixing niobium-based oxide and fibrous solid electrolyte and subjecting them to ball milling to obtain a mixed powder; heating the mixed powder in a protective atmosphere to obtain a composite material; mixing the composite material with a solvent and subjecting them to dispersion to obtain a functional slurry; S2, applying the functional slurry on the surface of the negative electrode plate to form a functional layer; and / or, applying the functional slurry on the surface of the separator to form a functional layer; S3. Prepare the positive electrode sheet, the separator and the negative electrode sheet into an electrode assembly, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, and the functional layer is provided between the separator and the negative electrode sheet.

7. The preparation method according to claim 6, characterized in that: In step S1, the conditions of the heating treatment include: a temperature of 600-800°C and a time of 120-168h; And / or, the dispersion treatment is ultrasonic dispersion, and the conditions of the ultrasonic dispersion include: ultrasonic frequency of 15-25KHz, dispersion time of 2-4h, power of 1-4KW; And / or, the solvent is polyvinylidene fluoride glue.

8. A battery, characterized in that: The battery comprises an electrode assembly, and the electrode assembly is the electrode assembly according to any one of claims 1 to 5 and / or the electrode assembly prepared by the preparation method according to claim 6 or 7.

Citation Information

Patent Citations

  • Carbon nano tube conductive agent sizing for negative electrode material of lithium ion battery and preparation method thereof

    CN108461753A

  • Negative electrode material layer, positive electrode material layer and semi-solid-state battery

    CN117334993A

  • Negative pole piece and electrochemical device and electronic device comprising same

    CN115280550A

  • Negative pole piece and electrochemical device

    CN117650227A

  • KR20210050059A